The Advanced Dietetics Module Development in Improving the Nutrition Diploma III Students’ Learning Outcomes of Kendari Health Polytechnic of the Ministry of Health - Rosnah Rosnah; P Petrus; Fonnie E. Hasan; Teguh Faturrahman; Rita Irma; Evi Kusumawati; I Made Rai Sudarsono (CV. Media Digital Publikasi Indonesia, 2023)
A successful learning process at schools must be supported by adequate facilities and infrastructure, including up-to-date learning resources and teaching materials that can support the learning process. The appropriate method in development research is a mixed method, which ensures that all research procedures are collected. Data analysis at the stage of the advanced dietetics module development process used analytical techniques in the forms of reviewing suggestions and corrections to the module content, presentation, language, and graphics. These processes were further conducted through a qualitative descriptive analysis. Material validation questionnaire sheets, linguists, and media were analyzed descriptively and quantitatively. In this case, calculation of the Likert Scale score was used to calculate this percentage. In addition, quantitative and descriptive analysis was carried out on student response questionnaires. The effectiveness of the advanced Dietetics module was evaluated quantitatively through quasi-experimental and non-equivalent control group research design. The expert team's assessment on the aspects of cover, content feasibility, presentation, module layout, graphics, and language aspects showed that all aspects were categorized as very feasible. Furthermore, in terms of appearance, presentation of material, and benefits, the results of the student's assessment on the module were categorized as very understandable. This study showed that the group of students who were given the dietetics module advanced had a higher average score. The researchers suggest that advanced dietetic modules need further development with regard to the media used to support teaching materials, for example interactive computer-based modules and multimedia products in digital formats (e-learning)